1985
DOI: 10.1246/cl.1985.739
|View full text |Cite
|
Sign up to set email alerts
|

ECKOLS, NOVEL PHLOROTANNINS WITH A DIBENZO-p-DIOXIN SKELETON POSSESSING INHIBITORY EFFECTS ON α2-MACROGLOBULIN FROM THE BROWN ALGA ECKLONIA KUROME OKAMURA

Abstract: Eckol, 2-phloroeckol and dieckol, novel phlorotannins with a dibenzo-p-dioxin skeleton have been isolated from the brown alga Ecklonia kurome Okamura as plasma α2-macroglobulin inhibitors and their structures have been determined on the basis of spectral data, in particular, by means of negative NOEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 6 publications
2
36
0
Order By: Relevance
“…Eisenine, biotin, and laminine are known components of this species 12) and eckol (1), 8,8Ј-bieckol (2), and phlorofucofuroeckol A (4) have been isolated from Ecklonia kurome OKAMURA as antiplasmin inhibitors. [8][9][10] Recently, it has been reported that phlorotannins from Ecklonia species are radical scavengers. 13,14) In this report, four phlorotannin compounds (1-4) containing the dibenzo [1,4]dioxin element as the core structure were isolated from E. cava and their inhibitory activities against HIV-1 RT and protease were evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eisenine, biotin, and laminine are known components of this species 12) and eckol (1), 8,8Ј-bieckol (2), and phlorofucofuroeckol A (4) have been isolated from Ecklonia kurome OKAMURA as antiplasmin inhibitors. [8][9][10] Recently, it has been reported that phlorotannins from Ecklonia species are radical scavengers. 13,14) In this report, four phlorotannin compounds (1-4) containing the dibenzo [1,4]dioxin element as the core structure were isolated from E. cava and their inhibitory activities against HIV-1 RT and protease were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The structures of these compounds were determined by comparison of UV, MS, and 1 H-and 13 C-NMR data with reported values. [8][9][10][11] Inhibitory Effects on HIV-1 RT and Protease Inhibitory activities of these compounds against HIV-1 RT and protease are shown in Table 1. 8,8Ј-Bieckol (2) and 8,4ٞ-dieckol (3) strongly inhibited HIV-1 RT activity, whereas eckol (1) and phlorofucofuroeckol A (4) did not exhibit inhibitory activity against this enzyme.…”
Section: Isolation Of Phlorotannins From E Cavamentioning
confidence: 99%
“…These algae are known to contain several phlorotannins, viz., eckol, 1) dieckol, 1) 6,6 0 -bieckol, 2) 8,8 0 -bieckol, 2) and phlorofucofuroeckol-A (PFF-A). 3) Phlorotannins have been reported to have certain biological activities, such as antioxidation, 4) bactericide, 5) anti-cancer, 6) anti-diabetic complications, 7,8) and chemoprevention against several vascular diseases.…”
mentioning
confidence: 99%
“…1). [5][6][7][8] Compound 1 was obtained as off-white amorphous powder. The molecular formula of 1 was determined as C 18 .…”
mentioning
confidence: 99%